Chapter Chronologie de Santa Maria Novella (1291-1319) - Carron, Delphine (Reti Medievali E-Book, 2020)
The identification of all the friars active in Santa Maria Novella on a regular basis or only temporarily is a puzzling issue, due to the high mobility of Dominican friars as well as the complexities of the internal organization of the convent. This contribution offers a schematic chronology of the Florentine Dominican convent of Santa Maria Novella between 1291 and 1319. For each year, the prior, the main lector, the lector of the Sentences, the students, and other friars active in the convent are listed, together with further information about the major events taking place at the convent.